IDENTIFYING COVIDOGENIC ENVIRONMENTS IN URBAN SECTORS OF KHROUB CITY (ALGERIA): A GIS-BASED APPROACH TO ASSESSING PANDEMIC RISK AND VULNERABILITY - Mouna Mazri,; Saif Eddine Chettah,; Manal Yahiouche, (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to assess the pandemic risk in the Algerian city of Khroub and develop a monitoring and health management tool to combat Covid-19 and other respiratory infections. To address the lack of statistical data at the micro-urban level, the authors conducted a household survey in Khroub between July and September 2022. The primary objective of this survey was to collect comprehensive data on vulnerability indicators at the scale of Khroub's urban sectors. The study utilized 13 indicators of vulnerability to Covid-19, selected from previous studies and research published by public health organizations and agencies. GIS technology was used to locate covidogenic environments (milieu) in Khroub, resulting in the creation of a GIS database called "Covidogenic Milieu." This study provides valuable insights for identifying vulnerable urban sectors and implementing adaptive measures to mitigate the effects of Covid-19. In the case of Khroub, the research also made relevant suggestions on how to address the identified vulnerability for the benefit of local authorities who commissioned this study.